Pemanfaatan video youtube sebagai media pembelajaran - Amalia, Oktavia (Maliki Interdisciplinary Journal, 2024)
YouTube is a medium that can be used to watch various video content, both video content and various tutorials such as make-up/beauty tutorials, cooking tutorials, and even videos for learning and other content are also available. This YouTube media is a supporting tool in implementing learning. As technology advances, technology becomes more sophisticated, which makes learning easier. Writing this article uses a qualitative research approach with an emphasis on descriptive analysis, which contains thoughts about several library sources (articles, books, slides, information from the internet, and so on). The purpose of writing this article is to find out the benefits of YouTube video media as a learning medium.